LINGUISTIC FEATURES OF HUMAN INTERNAL CONCEPTS IN ENGLISH AND UZBEK LANGUAGES - Rakhmatullayeva Guljakhon Normumin kizi (International Engineering Journal For Research & Development, 2022)
Linguistic approach to the study of linguistic units with national and cultural content, analysis of the national spirit of peoples reflected in world languages ​​and identification of ethnocultural features of linguistic expression in human relations are among the priorities in world linguistics. It should be noted that the main focus is on the functionality of language in the lives of different peoples, as well as its psycholinguistic, linguocognitive, lingvoculturological, and sociolinguistic nature.